Testicular transposition in children before scrotal external radiotherapy. Issue 9 (2nd July 2020) - Le Bon, Marielle; Lejeune, Herve; Helfre, Sylvie; Bolle, Stéphanie; Padovani, Laetitia; Mengue, Laurence; Corradini, Nadege; Hameury, Frédéric; Claude, Line
Abstract: Testicular transposition (TT) before scrotal external radiotherapy (RT) is poorly reported in children with cancer, with only rare case reports published. TT surgical techniques, dosimetric parameters, and testicular functions are retrospectively reported in 12 children, median age 12.8 years, after scrotal RT for sarcomas. TT has low morbidity and allows a dramatic RT dose decrease in the healthy testicle. Endocrine functions seem preserved while more follow‐up is needed to assess fertility. Though a rare situation, TT should be discussed in children and young adult cases when a scrotal high‐dose RT is needed.